Comparing Econometric Methods to Empirically Evaluate Job-Search Assistance - Paul Muller; Bas van der Klaauw; Arjan Heyma (Tinbergen Institute, 2017)
We test whether different empirical methods give different results when evaluating job-search assistance programs. Budgetary problems at the Dutch unemployment insurance (UI) administration in March 2010, caused a sharp drop in the availability of these programs. Using administrative data provided by the UI administration, we evaluate the effect of the program using (1) the policy discontinuity as a quasi-experiment, (2) conventional matching methods, and (3) the timing-of-events model. All three methods use the same data to consider the same program in the same setting, and also yield similar results. The program reduces job finding during the first six months after enrollment. At longer durations, the quasi-experimental estimates are not significantly different from zero, while the non-experimental methods show a small negative effect.
Keywords: J64; C14; C31; 330; empirical policy evaluation; job-search assistance; unemployment duration